2006
DOI: 10.3171/spi.2006.5.4.303
|View full text |Cite
|
Sign up to set email alerts
|

Technical description, phantom accuracy, and clinical feasibility for fiducial-free frameless real-time image-guided spinal radiosurgery

Abstract: Object The authors describe the technical application of the Xsight Spine Tracking System, data pertaining to accuracy obtained during phantom testing, and the initial clinical feasibility of using this fiducial-free alignment system with the CyberKnife in spinal radiosurgery. Methods The Xsight integrates with the CyberKnife radiosurgery system to eliminate the need for implantation of radiographic mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 13 publications
0
51
0
2
Order By: Relevance
“…The bony structure tracking includes skull tracking (6D Skull) and spine tracking 41,42 (XSight V R Spine). Soft tissue tracking (XSight V R Lung) uses density differences between the target and surrounding lung tissues without the need for invasive fiducial placement.…”
Section: Iiia1 Targeting Methodsmentioning
confidence: 99%
“…The bony structure tracking includes skull tracking (6D Skull) and spine tracking 41,42 (XSight V R Spine). Soft tissue tracking (XSight V R Lung) uses density differences between the target and surrounding lung tissues without the need for invasive fiducial placement.…”
Section: Iiia1 Targeting Methodsmentioning
confidence: 99%
“…The IGRT systems can be broken down into those based on stereoscopic xray-and CT-based imaging. For spine SBRT, the target can be positioned accurately to within 1-2 mm and 1°-2° with either IGRT system, 9,22,25,27,34 but there are inherent differences between the two that require discussion.…”
Section: Guidance With Ct-based or Stereoscopic X-ray Imaging To Verimentioning
confidence: 99%
“…5,[8][9][10][11][12][13][14][15][16][17] Although MR imaging is the best tool to evaluate the status of metastatic spinal tumors, many results about treatment efficacy are confined to clinical data such as pain control. 8,10,11,17 Some reports have included measurements of tumor volume by MR imaging but have not provided detailed MR imaging findings. 12,13,15,16 The life span of affected patients is limited, in most cases, by systemic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the technical feasibility and clinical efficacy of SRS for spinal metastatic tumors, and it has become a standard treatment for these tumors. 5,[8][9][10][11][12][13][14][15][16][17] The main goals of SRS in this setting are to arrest tumor growth throughout the patient's life (rather than cure the lesions), improve symptoms, and prevent the development or progression of neurologic deficits. Previously published reports about efficacy of SRS for spinal metastatic tumors are focused on just clinical data and outcome.…”
mentioning
confidence: 99%